Ilmu Pendidikan Islam Sebagai Perspektif Kehidupan - Ahmadi, Ahmadi (Tarbiyah STAIN Sorong, 2019)
Islamic Education as a basic capital in order to achieve happiness in human life in the world and the hereafter. Thus given the importance of Islamic Education, human beings need to get the need for this very important science as a basic provision to meet the level of happiness attainment away. Islamic Education is sourced from the Shari'a namely the Qur'an and Hadith. Because the Qur'an and the Hadith as the source of all knowledge that becomes the shari'a (rules) of Allah SWT, we are obliged to believe from the sources of shari'a that will be able and guarantee safety with human happiness. The system built by the Qur'an and the Hadith is the foundation of Islamic Education as a guarantee of Allah SWT in accordance with His pleasure. This type of research is descriptive qualitative research literature. The conclusion of this research is Islamic Education as the basis of human life, by consideration this has become a basic human need to achieve happiness both in the world and the hereafter. Islamic Education is sourced from the Shari'a namely the Qur'an and the Hadith that develops in the dynamics of human life in accordance with the atmosphere and development of the times that encourage the safety and happiness of humans for those who can support the application with the guidance of Islamic Education in accordance with sharia'.